The Impact Singer & Jipen of Dayak Tribe on Environmental Sustainability in Central of Borneo - Muh. Azhari (Talenta Publisher, 2019)
The environment is a mandate that must be maintained, because a good environment will produce a generation that is good and strong. Poor environmental management will create new problems. Ethics that regulate environmental management can maintain environmental conditions and reduce the rate of environmental change, for example by the presence of singer and jipen owned by the Central Of Borneo Dayak Tribe. Singer is a punishment and jipen is the amount of customary punishment given to someone who commits a customary offense. A detrimental activity will distrub the productivity of the environment, with the singer and jipen will be able to reduce the rate of damage. Case examples of the application of singer and jipen such as the Wilmar Group case, productive Durian Tree Cutting, Murder, even defamation, singer and jipen giving in accordance with the impact of the case, whether it is detrimental on a small or large scale and determined. The sentence was determined by the kepala adat / mantir / demang. The research used is a type of ethnography with data collection techniques by observation, interviews and literature studies. Keyword: Singer, Jipen, Dayak tribe & Environmental